Flexible/Stretchable Supercapacitors with Novel Functionality for Wearable Electronics - Keum, Kayeon; Kim, Jung Wook; Hong, Soo Yeong; Son, Jeong Gon; Lee, Sang-Soo; Ha, Jeong Sook (WILEY-V C H VERLAG GMBH, 2020)
With the miniaturization of personal wearable electronics, considerable effort has been expended to develop high-performance flexible/stretchable energy storage devices for powering integrated active devices. Supercapacitors can fulfill this role owing to their simple structures, high power density, and cyclic stability. Moreover, a high electrochemical performance can be achieved with flexible/stretchable supercapacitors, whose applications can be expanded through the introduction of additional novel functionalities. Here, recent advances in and future prospects for flexible/stretchable supercapacitors with innate functionalities are covered, including biodegradability, self-healing, shape memory, energy harvesting, and electrochromic and temperature tolerance, which can contribute to reducing e-waste, ensuring device integrity and performance, enabling device self-charging following exposure to surrounding stimuli, displaying the charge status, and maintaining the performance under a wide range of temperatures. Finally, the challenges and perspectives of high-performance all-in-one wearable systems with integrated functional supercapacitors for future practical application are discussed.
Keywords: REDUCED GRAPHENE OXIDE; HIGH-PERFORMANCE SUPERCAPACITOR; SOLID-STATE SUPERCAPACITORS; CAPACITIVE ENERGY-STORAGE; GEL POLYMER ELECTROLYTE; THIN-FILM NANOGENERATOR; MICRO-SUPERCAPACITORS; FLEXIBLE SUPERCAPACITORS; IONIC LIQUID; ELECTROCHROMIC SUPERCAPACITOR